Characterization of a new fusicoccane-type diterpene synthase and an associated P450 enzyme - Huang, Jia-Hua; Lv, Jian-Ming; Xiao, Liang-Yan; Xu, Qian; Lin, Fu-Long; Wang, Gao-Qian; Chen, Guo-Dong; Qin, Sheng-Ying; Hu, Dan; Gao, Hao (Beilstein Journal of Organic Chemistry, 2022)
Fusicoccane-type terpenoids are a subgroup of diterpenoids featured with a unique 5-8-5 ring system. They are widely distributed in nature and possess a variety of biological activities. Up to date, only five fusicoccane-type diterpene synthases have been identified. Here, we identify a two-gene biosynthetic gene cluster containing a new fusicoccane-type diterpene synthase gene tadA and an associated cytochrome P450 gene tadB from Talaromyces wortmannii ATCC 26942. Heterologous expression reveals that TadA catalyzes the formation of a new fusicoccane-type diterpene talaro-7,13-diene. D2O isotope labeling combined with site-directed mutagenesis indicates that TadA might employ a different C2,6 cyclization strategy from the known fusicoccane-type diterpene synthases, in which a neutral intermediate is firstly formed and then protonated by an environmental proton. In addition, we demonstrate that the associated cytochrome P450 enzyme TadB is able to catalyze multiple oxidation of talaro-7,13-diene to yield talaro-6,13-dien-5,8-dione.
Keywords: cytochrome P450 enzyme; diterpene synthase; gene cluster; genome mining; site-directed mutagenesis